The formalism of governance on the performance of family SMEs in Chad - Ratangar, Djimnadjingar; Besson, Dominique (Asian Journal of Empirical Research, 2024)
The aim of this study is to analyze the effects of family SME governance on their performance. Thus, the concern of this work is to present the most relevant agency relationships for analyzing the governance of family SMEs and the family factors that can be analyzed from the theoretical framework of agency and stewardship, given the limitations of agency theory for the study of family SME governance. The study is based on a sample of 182 Chadian family SMEs from a variety of sectors. The investigation is based on a hypothetico-deductive method, and the research results show that the impact of governance on performance is significant. A Principal Component Analysis (PCA) was carried out to identify specific factors for the three groups of variables: governance, altruism and family traits. Factor regression by respective degree of significance and importance of the factors shows that the factors governance formalism, relationships and delegations, internal relationships, training and experience and professional conflicts are the main drivers of SME performance. Finally, the impact of the altruism variable on performance is insignificant. In conclusion, the theoretical and managerial implications are discussed, along with the main avenues for future research.